PENGARUH AKTIVITAS FISIK DAN LINGKUNGAN ALAMIAH BAGI DAYA TAHAN TUBUH ANAK USIA DINI - Elfan Fanhas Fatwa Khomaeny; Maulidya Ulfah; Nur Hamzah (AWLADY : Jurnal Pendidikan Anak, 2020)
This research aims to determine the influence of physical activity and the provision of the natural environment for early childhood endurance because many schools for early childhood in Indonesia, are less optimal in the habituation of physical activities and less concerned with the natural environment. Their focus only on the children's Activities program based on the rigid curriculum, place, and learning media, with all activities held in the room. According to the interview and observation result in Daycare Tunas Mentari. The habituation of physical activity and the provision of natural environment had a significant influence on the children's body's endurance. Habituation of physical activity for early childhood must be done programmatically and become a habit; also the intervention of natural environment in schools must be done, by planting fruit trees or large trees that have the function of oxygen producers, neutralize pollution, cleanse and stabilize the air temperature, maintain clean water reserves, and control ecological, social imbalance. Types of trees and plants must be the suitability of their environment. Caring for the natural environment is very beneficial for the development and health of children, also for the sustainability of the universe and the health of the World Society